4-Amino-3-(3-methoxybenzyl)-1H-1,2,4-triazole-5(4H)-thione - Hegde, Gurumurthy; Sarojini, B. K.; Manjula, P. S.; Kour, Dalbir; Anthal, Sumati; Gupta, Vivek K.; Kant, Rajni (International Union of Crystallography, 2013)
In the title molecule, C10H12N4SO, the triazole ring forms a dihedral angle of 73.0 (5) with the benzene ring. The methoxy group is approximtely coplanar with the benzene ring with a C. . .C—O—Cmethyl torsion angle of 4.7 (3). In the crystal, N— H S hydrogen bonds connect pairs of inversion-related molecules, which are in turn connected by N—H N hydrogen bonds into chains of rings along [010]. Weak C— H O hydrogen bonds connect these chains into a twodimensional network parallel to (102).